Antioxidants: Stimulus‐Responsive Anti‐Oxidizing Drug Crystals and their Ecological Implication (Small 21/2019). Issue 21 (24th May 2019) - Kim, Byoung Soo; Leong, Jiayu; Yu, Seung Jung; Cho, Younghak; Park, Chang Gyun; Kim, Da‐Hye; Ko, Eunkyung; Im, Sung Gap; Lee, Jonghwi; Kim, Young Jun; Kong, Hyunjoon
Abstract : In article number1900765, Jonghwi Lee, Young Jun Kim, Hyunjoon Kong, and co‐workers assemble a new drug‐delivery system prepared with stimulus‐responsive crystallized catechin–an antioxidant found in green tea and fruit–that can dissolve when the hydrogen peroxide level increases abnormally and restore the heart rate of water fleas.